Intensifikasi Sintesis Diasetin dan Triasetin melalui Esterifikasi Gliserol dengan Katalis Berbasis Daun Bambu - Fitri, Maysa; Syamsuddin, Yanna; Suriaini, Nanda; Marwan (REACTOR: Journal of Research on Chemistry and Engineering, 2024)
The synthesis of acetins from glycerol is achieved through esterification assisted by a solid acid catalyst and microwave irradiation. Diacetin and triacetin, suitable as biofuel additives, are produced using biogenic silica from bamboo leaves, which is chemically activated with strong acid and calcined. No research has utilized silica catalysts derived from bamboo leaf ash to produce diacetin and triacetin. This study aims to employ bamboo leaf-based heterogeneous catalysts to enhance triacetin selectivity, simplify product purification and separation, and enable catalyst reuse. Furthermore, microwave application can accelerate the reaction time. The best total selectivity for diacetin and triacetin was obtained under operating conditions of 3% catalyst concentration, a 1:6 molar ratio, and 60 minutes of microwave irradiation. The yields of diacetin and triacetin under these conditions were 65.80% and 18.70%, respectively. GC-MS and FTIR analysis confirm the presence of monoacetin, diacetin, and triacetin, with a total selectivity for diacetin and triacetin of 84,50%.